Usaha-Usaha Dalam Penjualan Produk (Studi Kasus: Sosis Champ PT PrimaFood) - Alifia Putri Febrika; Haura Dwika Priandini; Lutfiah Maulani Saputri; Mahendrati Sekar Palupi; Naerul Edwin Kiky Apriyanto; Siska Eristina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Sales believes that more aggressive advertising and selling is needed because not enough customers or businesses are buying the goods offered by an organization on a regular basis. In the face of increasingly fierce market competition, this study investigates the sales strategy of PT Primafood Internasional's Champ brand instant sausage product. PT Primafood tries to implement an effective marketing strategy to increase sales due to the increasing demand for food products, especially animal products. The results of the analysis show that the competitive market structure affects the way the company markets its products. Through creative promotions and effective distribution, PT Primafood has succeeded in increasing brand awareness and sales. This study makes a significant contribution to the process of developing marketing strategies in the Indonesian processed food industry and suggests a method that is more sensitive to changes in consumer preferences.